A new method for inoculation of fruit with Guignardia citricarpa, the causal agent of citrus black spot - Baldassari, Ricardo B. [UNESP]; Reis, Renato F. [UNESP]; de Goes, Antonio [UNESP] (Springer, 2009)
Citrus black spot (CBS) is a fungal disease, caused by Guignardia citricarpa, that has a high economic impact on citrus. Although G. citricarpa has been associated with black spot of citrus, an adequate pathogenicity test is still not available. Thus, our objective was to develop and evaluate a simple, safe, and practical pathogenicity test. We used fruits from Pera-Rio and Valencia sweet orange trees from two different orchards, located in the State of São Paulo, Brazil. Inoculation was performed by placing six disks colonized by G. citricarpa, onto the peel of healthy fruits, previously bagged. In the Pera-Rio sweet orange grove, initial symptoms of the false melanose type resulting from the inoculations were observed 55 days after inoculation (dai). In the Valencia grove, initial symptoms also of the false melanose type resulting from the inoculations occurred 73 dai. A total of 92.8% and 86.6% of the Pera Rio and Valencia fruits inoculated, respectively, showed symptoms of CBS. Citrus black spot symptoms were not observed in any of the control fruits.
Keywords: Citrus sinensis; Phyllosticta citricarpa; Pathogenicity